The mid‐point transverse process to pleura (MTP) block: a new end‐point for thoracic paravertebral block1. (1st August 2017) - Costache, I.; de Neumann, L.; Ramnanan, C. J.; Goodwin, S. L.; Pawa, A.; Abdallah, F. W.; McCartney, C. J. L.
Summary: Current descriptions of thoracic paravertebral block techniques require the needle tip to be anterior to the superior costotransverse ligament. We hypothesised that an injection point midway between the posterior border of the transverse process and the pleura would result in spread to the paravertebral space. We completed bilateral injections of 5 ml methylene blue 0.2% midway between the posterior border of the transverse process and the pleura at T2, T4, T6, T8 and T10 in three unembalmed cadavers. The presence of methylene blue dye at the nerve root in the paravertebral space, the corresponding intercostal nerve and sympathetic chain at the level of injection, and at additional levels, was examined. We identified the superior costotransverse ligament, pleural displacement and spread to the erector spinae plane. We describe two case reports using this technique in patients. Our cadaver results and clinical cases demonstrate that, with the exception of cadaver 1, an injection point midway between the posterior border of the transverse process and pleura consistently achieved spread of dye at least to the paravertebral space at the level of injection, and frequently to adjacent levels. This may be a plausible explanation for the landmark technique's inability to reliably achieve a multilevel block. We describe a new ultrasound‐guided technique for a single level paravertebral block.